Penguatan Literasi Perkembangan Anak Usia Dini bagi Pengasuh Daycare di Posyandu Mawar Desa Tampingan Kabupaten Kendal - Ansor, Basirudin; Devina Puspa Wulandari; Aditya Putra Ramdani; Achmad Solichan; Kilala Mahadewi; Muchamad Faris Chakim (Jurnal Pengabdian Masyarakat Waradin, 2025)
Improving caregiver literacy regarding early childhood development is a strategic step to ensure optimal child growth and development. This educational activity was conducted at the Mawar Integrated Health Post (Posyandu Mawar), Tampingan Village, Boja District, involving 20 caregivers as active participants. The series of activities were systematically arranged, including a pre-test to determine the level of initial understanding, counseling through a lecture method accompanied by comprehensive material delivery, interactive discussions that allowed participants to exchange experiences, practice of child development stimulation as a form of direct skills, and a post-test to assess improvements in learning outcomes. The analysis results showed that the educational activity had a significant impact on improving caregiver literacy. The average pre-test score of 53.25 (SD = 9.54) increased to 69.60 (SD = 10.30) in the post-test. The average difference of 16.35 (SD = 5.84) with a 95% confidence interval between 13.62–19.08 indicated a significant increase. The paired t-test yielded a value of t(19) = 12.515 with p < 0.05, confirming a significant difference between the scores before and after the program. The percentage increase of 30.7% indicates the effectiveness of the applied educational method. The recommendation from this activity is the need to develop an educational program that is carried out in a sustainable and structured manner, accompanied by mentoring involving health workers, PAUD educators, and support from the village government, so that caregiver literacy can continue to increase and optimal child growth and development can be guaranteed from an early age.